Nudibranchia from the remote southern Chilean Guamblin and Ipún islands (Chonos Archipelago, 44-45° S), with re-description of Rostanga pulchra MacFarland, 1905 Nudibranquios de las islas Guamblin e Ipún (Archipiélago de los Chonos 44-45° S) con redescripción de Rostanga pulchra MacFarland, 1905 - MICHAEL SCHRÖDL; JOSÉ H GRAU (Revista Chilena de Historia Natural, 2006)
The southern Chilean archipelago and fjordland (41-52° S) thus far is very poorly investigated also with regard to its nudibranch fauna. This study presents the first records of nudibranchs from remote islands of the Chonos archipelago exposed to the open Pacific. Collecting data and some biological observations are given for the doridoidean Archidoris fontaini, Diaulula punctuolata and Rostanga pulchra. Taxonomically relevant external and radular characters of R. pulchra are redescribed and compared with literature data on conspecifics from Argentina and California. The bipolar, cold-water adapted R. pulchra is critically compared with the western Atlantic, warm-water adapted R. byga. New distributional data indicates that the Chiloé Island area (41-43° S) does not represent a strict southern distributional barrier for warm-temperate eastern Pacific nudibranch species but is at least partly due to collecting bias Los archipiélagos y fiordos del sur de Chile han sido muy poco estudiados y particularmente la fauna de nudibranquios. En este estudio se presentan los primeros registros de nudibranquios para islas del Archipiélago de los Chonos abiertas al Pacífico. Se indican datos de recolecta y algunas observaciones biológicas para los doridáceos Archidoris fontaini, Diaulula punctuolata y Rostanga pulchra. La morfología externa y caracteres radulares de R. pulchra son redescritos y comparados con literatura referente a ejemplares de Argentina y California. Se comparan críticamente R. byga de las aguas cálidas del Atlántico occidental con R. pulchra , especie bipolar adaptada a aguas frías. La nueva información distribucional indica que la isla de Chiloé no representa una barrera distribucional estricta para las especies de nudibranquios del Pacífico sudeste, y es en su mayor parte debido a un vacío de recolección